Synopsis of the Japanese species of Aleocharinae (Coleoptera: Staphylinidae), with review of the type specimens I. Tribes Himalusini and Leucocraspedini - Maruyama, Munetoshi; Yamamoto, Shûhei; Eldredge, Taro K. (Zootaxa, 2014)
The Japanese species of the tribes Himalusini and Leucocraspedini are reviewed. The tribe Sinanarchusini Pace, 2013 is synonymized with Himalusini in which the genera Protinodes Sharp, 1888, Himalusa Pace, 2006 and Sinanarchusa Pace, 2013 are recognized. Protinodes and Sinanarchusa have been placed in Hygronomini and Sinanarchusini respectively. Only a single species Leucocraspedum rufotestaceum Bernhauer, 1927 is recognized in Japanese fauna of Leucocraspedini. Two other known species, Leucocraspedum pallidum Cameron, 1933 and L. parvum Cameron, 1949 are synonymized with L. rufotestaceum.